Disfunción inmunológica en enfermedad de Alzheimer; proinflamatoria en etapas iniciales y regulatoria, y exhausta en etapas avanzadas - Romero U., César Antonio; Rogers C., Nicole; San Martín R., Carol; López N., Mercedes; Behrens P., María Isabel (Revista Hospital Clínico Universidad de Chile, 2022)
Alzheimer disease (AD) is the main cause of dementia worldwide and a source of important population morbidity and mortality. It is estimate that its prevalence will increase dramatically in the upcoming years. The classical clinical presentation of AD is an amnesic hippocampal syndrome, and Mild Cognitive impairment (MCI) is considered the initial stage between normal cognition and dementia. The most accepted pathogenesis establishes amyloid beta (Ab) deposition in brain parenchyma as the initial mechanism, followed by the intracellular accumulation of hyperphosphorylated tau finally leading to the loss of synapses and neurons. Recently, the study of AD pathogenesis is focusing on immune mechanisms as main actors of disease development. Microglia is the macrophagic resident cell in the central nervous system (CNS), and initiates the inflammatory response and Ab phagocytosis, interacting with other glia and recruiting diverse immune cells to the CNS. The role of the adaptive immune system, and, especially T lymphocytes’ role, is still controversial. We hypothesize that the pathogenesis of AD is dynamic; with a preponderant proinflammatory activity initially, but later on, the persistent presence of Ab due to the lack of its proper elimination leads to a phenomena of lymphocyte dysfunction and immunological tolerance that have a deleterious role at advanced stages of the disease.